The Potential Role of Traditional Food in Stunting Prevention in Indonesia; An Expert Consensus - Musiawan, Ria; Wagiu Basrowi, Ray; Jatiningrum, Hindah; Sarinastiti, Nia; Wulandari, Alifah (Ridwan Institute, 2023)
Indonesia has projected to accelerate stunting reduction to 14% by 2024. Multiform interventions and collaboration among institutions or organizations have already been made to tackle the underlying determinants of stunting. This paper review was to explore the traditional food that may potentially help to accelerate progress towards stunting reduction. The results of an expert meeting of the “Declaration of Consensus Nutrition and Hydration based on Traditional Foods” suggested developing an innovative strategy to support the Government of Indonesia in National Strategy stunting reduction. The essential of the first 1000 days of a child’s life particularly in feeding practice to infants aged 6 months with a required on rich macro and micronutrients, home-cooked and derived from traditional foods. Traditional foods have relatively acceptable and affordable with complete nutrients. Growing evidence shows the relationship between local foods and child nutrition status.